2020
DOI: 10.1039/d0sc01676d
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibitors: review and new strategies

Abstract: The search is on for effective specific inhibitors for PI3Kα mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 126 publications
2
106
0
1
Order By: Relevance
“…To investigate the PI3K/AKT pathway, cells prepared as above were pre-treated for 1 h with LY294002 (5 µM). This inhibitor was chosen as it inhibits all class I PI3Ks, which are the most relevant for cell physiology [ 50 ]. Mycoplasma testing was routinely done with the N-GARDE Mycoplasma PCR Reagent set (Euro Clone, cat.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the PI3K/AKT pathway, cells prepared as above were pre-treated for 1 h with LY294002 (5 µM). This inhibitor was chosen as it inhibits all class I PI3Ks, which are the most relevant for cell physiology [ 50 ]. Mycoplasma testing was routinely done with the N-GARDE Mycoplasma PCR Reagent set (Euro Clone, cat.…”
Section: Methodsmentioning
confidence: 99%
“…The safety profile of inhibitors is acceptable [77]. Single-agent PI3K inhibitor does not present a potent effect like EGFR-TKI and works on the selected tumor [77][78][79][80]. FDA only approves alpelisib for breast cancer in PI3K mutated breast cancer and paxalisib for DIPG.…”
Section: Pi3k Inhibitors Are Promising But Still Have a Long Way To Gomentioning
confidence: 99%
“…Scholars note that PIK3CA mutations often coexist with KRAS and BRAF mutations [94]. A parallel oncogenic pathway activation abrogates the effects of PI3K/Akt/mTOR inhibitors [77,79]. Vemurafenib and dabrafenib are two successful drugs targeting BRAF; however, they present a very modest effect and only last 6 months PFS [95][96][97][98].…”
Section: Synthetic Lethal With Pi3k Inhibitors May Be Highlighted Formentioning
confidence: 99%
“…The selection of PI3Kδ can be related with the expression pattern of this isoform, which is restricted to immune system. The PI3Kα is widely expressed in the body and also is related with the insulin signaling pathway and is related with the hyperglycemia [29,30,32] . They observed that the carbonyl and fluoro group in the quinazolinone extended into the solvent exposed region and enabled the introduction of the HDAC pharmacophore (linker and zinc binding group) [119] (Figure 11).…”
Section: Exploring Selectivity In Multitarget Hdac and Pi3k Inhibitorsmentioning
confidence: 99%
“…PI3Ks are a family of lipid kinases that integrate signals that regulate multiple signaling pathways in several cellular processes, such as cell proliferation, growth, survival, motility and metabolism [28–32] . Changes that cause PI3K overactivation are frequently found in many types of cancer, which makes this class of enzymes an interesting target for the development of new inhibitors as a promising anticancer therapy [33–36] .…”
Section: Introductionmentioning
confidence: 99%